A experimentação na formação de professores de Química: um discurso em ação - Frozza, Edson (2018)
Discourse about experimentation in training Chemistry teachers‘ courses is presented in this dissertation. The outcomes of the study suggest that practices developed in teaching Chemistry are guided by the discourse in the university level, as well as in Basic Education. The discussion is supported by and appropriated from Michel Foucault and others authors, specially in terms of archaeological processes. In this theoretical and methodological process of Discourse Analysis, discourse is understood as practice. In this sense, produces effects on practices and actions as it is produced, reproduced, intensified by them. The analysis included interviews with teachers who teach experimental Chemistry classes in the graduation course in Chemistry at the Federal University of Pelotas, official documents that guide the training courses for teachers and a group of materials and productions in the field of Chemical Education. From the analysis developed, the emergence of a statement that at all time is put into action, updated and reinforced, has been evidenced, which can be described as: experimentation is marked by elements and processes that systematically seek to differentiate and separate from theory in level of university education. There is a discourse that puts into play certain practices that guide the processes and activities developed in the experimental classes, as well as in the course organization itself. Therefore, it is important to rethink the practices developed and naturalized in the training courses for chemistry teachers.